Simptom Disleksia kanak-kanak prasekolah - Rohaty Mohd Majzub, -; Shafie Mohd. Nor, - (penerbit ukm, 2005)
This study is to identify dyslexia symptom among forty preschoolers from selected kindergartens in Negeri Sembilan. The instrument of the study was adapted from ‘The Dyslexia Early Screening Test (DEST) renamed ‘Ujian Awal Pengesahan Disleksia’. The instrument included ten subtests including rhyme detection, memory recall, fine motor skills, sense perception, and posture stability. The sample of the study is chosen through random sampling from two schools in Negeri Sembilan. The data was analyzed descriptively using percentages. The findings of the study indicated that 27.5% of the preschoolers had dyslexic symptoms; 15 % were identified as having high risk of dyslexic symptoms. More boys had dyslexic symptoms (10%) compared to girls (5%).The three subtests that showed low scores were letter naming, rhyme detection, and phonological discrimination. Results indicated urgent need to train parents to interact with dyslexic children at home. It also suggested that teacher training addresses strategies to overcome difficulties facing dyslexic children.